How can transforming representation of mathematical entities help us employ more cognitive resources? - Khatin-Zadeh, Omid; Farsani, Danyal; Breda, Adriana (Frontiers in Psychology, 2023)
This article discusses the cognitive process of transforming one representation of mathematical entities into another representation. This process, which can be called mathematical metaphor, allows us to understand and embody a difficult-to-understand mathematical entity in terms of an easy-to-understand entity. When one representation of a mathematical entity is tranformed into another representation, more cognitive resources such as the visual and motor systems can come into play to understand the target entity. Because of their nature, some curves, which are one group of visual representations, may have a great motor strength. It is suggested that directedness, straightness, length, and thinness are some possible features that determine degree of motor strength of a curve. Another possible factor that determines motor strength of a curve is the strength of association between shape of the curve and past experiences of the observer. If an individual has had the repetitive experience of observing objects moving along a certain curve, the shape of the curve may have a great motor strength for her/him. In fact, it can be said that some kind of metonymic relationship may be formed between the shapes of some curves and movement experiences.